Sociocultural predictors of immigrant adjustment and well-being - Shekriladze, Ia; Javakhishvili, Nino (Frontiers in Sociology, 2024)
Introduction Research shows that culture change may pose risks to immigrant wellbeing. Our study examined adult Georgians (N = 431) residing in Greece, Italy, and Germany, and explored associations between their demographic characteristics, sociocultural adjustment, and psychological well-being outcomes. Methods Conducted via electronic self-report survey, the cross-sectional study measured participants’ levels of sociocultural adjustment, psychological adjustment, and depression along with the willingness to interact with host nationals, perceived sense of discrimination, history of being undocumented, age and length of relocation, and fluency in host language. The study also examined differences in three subsamples from the standpoint of intercultural distance. Sociocultural Adjustment Scale, Brief Psychological Adaptation Scale, Center for Epidemiologic Studies Depression Scale and Host Interaction Scale were used to measure the corresponding variables. Perceived history of discrimination was measured by a Likert-scale question about discrimination in a host country. Intercultural distance was established by Hofstede cultural compass and was estimated to be the smallest with Greece and the largest with Germany. Results Depression was positively predicted by histories of discrimination and illegal immigration, host language fluency upon relocation, and was negatively predicted by sociocultural adjustment. Psychological adjustment was positively predicted by sociocultural adjustment, willingness to interact with host nationals, and ongoing language fluency, while perceived sense of discrimination, age, and poor financial state acted as negative predictors. Finally, sociocultural adjustment acted as the strongest determinant of wellbeing predicting both lower depression and higher psychological adjustment. Discussion Our findings suggested that adjustment in diverse sociocultural domains was the most critical for the immigrants’ psychological well-being along with the lack of perceived discrimination. Additional factors associated with the better adaptation outcomes included younger age, willingness to interact with host nationals, language fluency, better financial standing and no history of being undocumented. The results also indicated that host language proficiency upon relocation may contribute to migrant susceptibility, whereas intercultural distance may be overshadowed in importance by acculturation conditions. The findings illustrate the complexity of migration and culture change and point to the superiority of wholistic policies and practices in promoting smooth transition of immigrant populations.